Avaliação da usabilidade de representações cartográficas em diferentes escalas para sistema de navegação e guia de rota em automóvel - Ramos, Ana Paula Marques [UNESP] (2015)
Driver safety issue related to interaction with in-vehicle Route Guidance and Navigation Systems (RGNS) refers to one of the most relevant concern at the Human-Machine Interaction area. Researches which determine efficient and effective ways to present navigation information for drivers are becoming more necessary recently. This is mainly because route guidance systems have been adopted more often by drivers due to the mobility they offer. It is known that noises in the information communication process in interfaces of route guidance systems has overloaded drivers' cognitive processing system and maximized the traffic accidents chances. Thus facilitate the navigation task development and do not cause risks to driving task have been the aim of several investigations in different parts of the world. Among efforts to solve these noises in communication information process it should be highlighted map scale selection. Map scale selection according to user's demand may favour the information comprehension quickly, and this may imply less distraction of drivers on road. However, have been noted that, to select scales for maps of RGNS, it has not been considered both the different stages involved in navigation task and the use of audio-dynamic map in heading-up orientation (egocentric view) to present information for drivers. Therefore, the following question is addressed: ''To what extent does scale interferes on usability of audio-dynamic maps, in heading-up orientation, when drivers perform the tactical task in urban areas?. The aim of this research is to evaluate usability of cartographic representations at different scales for a prototype of route guidance and navigation system. Several experiments were performed with drivers to treat this research problem including a driving simulator experiment...